O knjigi (Ustavno)sodno odločanje - Sovdat, Jadranka (Pravnik, 2014)
The book provides various perspectives on the importance, substance, and methods of judicial decision-making before constitutional and regular courts. In the first part, the authors analyse the judiciary as a social subsystem as well as judicial ethics. By means of the argumentation theory, with an emphasis on the requirement of ensuring a constitutionally consistent interpretation of laws, they assess fundamental questions regarding the interpretation of legal texts. The authors present the development and application of the principle of proportionality in constitutional case law and the influence of past decisions on judicial decision-making. In the second part, the authors evaluate the application of the principle of good faith and fairness in adjudication as well as selected aspects of tort law. They analyse decisions of the Constitutional Court of the Republic of Slovenia regarding social security and the determination of parenthood. In the final part, the authors address the relationship between European Union law and national constitutional law, the influence of the decisions of the European Court of Human Rights on domestic case law, the principles of the international law as a criterion for judicial assessment, and legal interest as a procedural prerequisite for judicial assessment.
Keywords: (Ustavno)sodno odločanje; ocene in poročila; sodna praksa; sodno odločanje; ustavno pravo